2021
DOI: 10.1542/peds.2020-049411
|View full text |Cite|
|
Sign up to set email alerts
|

Sexual and Reproductive Health Discussions During Preventive Visits

Abstract: OBJECTIVES: To quantify adolescent-and parent-perceived importance of provider-adolescent discussions about sexual and reproductive health (SRH), describe prevalence of provider confidentiality practices and provider-adolescent discussions about SRH topics during preventive visits, and identify missed opportunities for such conversations. METHODS:We used data from a national Internet survey of 11-to 17-year-old adolescents and their parents. Data were weighted to represent the noninstitutionalized US adolescen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 25 publications
0
25
0
Order By: Relevance
“…10 The discussion of sensitive topics is also limited, with few adolescents admitting to discussing sexual and reproductive health topics other than puberty at their most recent preventive visit. 11 Issues related to confidentiality are particularly relevant in emergency departments (EDs). Prior studies suggest that ED HCPs often forego confidential conversations about sensitive topics, even when they perceive them potentially necessary for their patient's clinical care.…”
Section: Introductionmentioning
confidence: 99%
“…10 The discussion of sensitive topics is also limited, with few adolescents admitting to discussing sexual and reproductive health topics other than puberty at their most recent preventive visit. 11 Issues related to confidentiality are particularly relevant in emergency departments (EDs). Prior studies suggest that ED HCPs often forego confidential conversations about sensitive topics, even when they perceive them potentially necessary for their patient's clinical care.…”
Section: Introductionmentioning
confidence: 99%
“…13 International studies have concluded that adolescents would like healthcare providers to address sexuality issues, and that they prefer to discuss sensitive topics directly. 4,14,15 However, young people's experiences of being asked about sexual risk-taking and sexual ill health, in a context of systematic assessment within health care, have not, to our knowledge, been previously investigated. The aim of this study was therefore to explore youth clinic visitors' experiences of systematic assessment of sexual ill health and risk-taking using SEXIT, and specifically of filling out the SEXIT questionnaire.…”
Section: Introductionmentioning
confidence: 99%
“…In previous work, we have explored a triadic model, recognizing the complex relationship between parents, adolescent patients, and clinicians [5]. Parents select how and where most adolescents get routine healthcare, and this model reflects the partnership parents expect with pediatricians, family physicians, or other clinicians caring for their teens.…”
mentioning
confidence: 99%